1996
DOI: 10.1161/01.hyp.27.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in Cardiac Structure After Treatment in Secondary Hypertension

Abstract: To investigate the role of aldosterone and the renin-angiotensin system in cardiac structure, we performed echocardiography in patients with secondary hypertension. The relation between blood pressure or hormonal influences and left ventricular hypertrophy has not been well established in secondary hypertension. Sixteen patients with primary aldosteronism and 11 with unilateral renovascular hypertension who had completely normalized blood pressure after operation or percutaneous transluminal angioplasty were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
1
26
1
Order By: Relevance
“…[2][3][4]9,[19][20][21][22][23][24][25][26][27][28] Cardiac fibrosis with ensuing altered LV diastolic dysfunction can lead to left atrium dilatation and increased risk of atrial fibrillation (AF) 7,8,29 ; whether these changes regress with specific treatment for PA remains uncertain. 3,4,19,20,26 We, therefore, set out to prospectively investigate the long-term effects of correction of hyperaldosteronism on BP, LV mass, and cardiovascular events in a large cohort of patients with PA.Abstract-Primary aldosteronism (PA), a common cause of high blood pressure (BP), induces left ventricular (LV) hypertrophy and an excess rate of cardiovascular events. Whether its treatment provides long-term cure of hypertension and regression of cardiovascular damage remains uncertain.…”
mentioning
confidence: 99%
“…[2][3][4]9,[19][20][21][22][23][24][25][26][27][28] Cardiac fibrosis with ensuing altered LV diastolic dysfunction can lead to left atrium dilatation and increased risk of atrial fibrillation (AF) 7,8,29 ; whether these changes regress with specific treatment for PA remains uncertain. 3,4,19,20,26 We, therefore, set out to prospectively investigate the long-term effects of correction of hyperaldosteronism on BP, LV mass, and cardiovascular events in a large cohort of patients with PA.Abstract-Primary aldosteronism (PA), a common cause of high blood pressure (BP), induces left ventricular (LV) hypertrophy and an excess rate of cardiovascular events. Whether its treatment provides long-term cure of hypertension and regression of cardiovascular damage remains uncertain.…”
mentioning
confidence: 99%
“…Various populations have been studied, ie, young healthy adults, 20 employed subjects 16 or middle-aged men in a general population, 15 children and adolescents 18 or adults with essential hypertension, 13,14,17,19,22 and patients with renovascular hypertension. 21 Most authors did not observe a significant relationship of left ventricular mass (index) or wall thickness, or both, with plasma renin activity. [13][14][15]17,18,21 Left ventricular mass (index) correlated significantly though weakly (0.30 Ͻ r Ͻ 0.35) with plasma renin activity in one report in young healthy adults 20 and another in hypertensives 19 but independence of possible confounding factors was not assessed.…”
Section: Discussionmentioning
confidence: 95%
“…21 Most authors did not observe a significant relationship of left ventricular mass (index) or wall thickness, or both, with plasma renin activity. [13][14][15]17,18,21 Left ventricular mass (index) correlated significantly though weakly (0.30 Ͻ r Ͻ 0.35) with plasma renin activity in one report in young healthy adults 20 and another in hypertensives 19 but independence of possible confounding factors was not assessed. By contrast, stepwise multiple logistic regression revealed that left ventricular hypertrophy was even associated with low renin levels in patients with sustained hypertension.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations